Tools : the ultimate guide - Waldman, Jeff (Chronicle Books, 2022)
"Featuring over 500 entries on tools categorized by function, Compendium of Tools is a celebration of home improvement and skilled craftwork. The book covers a variety of tools used by amateurs, both hand tools and power tools, and offers some background information, interesting history, care tips, advice on what projects they are best for, and suggestions of other similar tools to consider adding to a collection. With detailed entries and illustrations, the book is packed with wisdom that is as inspirational as it is practical"--